Introduction to the Special Issue Migrants and the Criminal Courts in Western Europe, 1600-1900 - Marion Pluskota (Tijdschrift voor Sociale en Economische Geschiedenis, 2023)
This special issue aims to shed light on a still understudied subject: how migrants were treated by the courts when they committed a crime. Historians of crime and migration, social scientists, and criminologists have produced essential research on the criminalization of migration over the centuries, and on how the mobility of the poorest became a contentious issue for the local and national authorities.